Description of Female Students Skills in Carrying Out Endorphin Massage Techniques to Reduce Menstrual Pain - Septiani, Hani; Lestari, Lusi; Ariani, Dini; Heryani, Sri (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2024)
Introduction: Menstrual pain is pain felt during the menstrual cycle. The prevalence of primary Menstrual pain is generally experienced by adolescent girls aged 17-24 years by 67-90%. Menstrual pain has been identified as the most common menstruation-related cause of short-term school absenteeism among young girls. So menstrual pain in adolescents needs attention and information to provide appropriate treatment both pharmacologically and non-pharmacologically. Pharmacological treatment for menstrual pain can be overcome with analgesic drugs but causes addiction and dangerous side effects. One effective way to prevent menstrual pain is relaxation in the form of hand massage with endorphin massage techniques. This technique increases the release of endorphin and oxytocin hormones which function to reduce pain and based on research results show that the effectiveness of endorphin massage is more effective in reducing pain. Objective: The purpose of this research is to determine the description of female students' skills in carrying out endorphin massage techniques to relieve menstrual pain. Method: This study uses a descriptive research design. The sample in this study was determined using a quota sampling technique, namely as many as 32 respondents who fit the inclusion criteria. Result: The result of the research that respondents were able to carry out more endorphin massage technique, namely 20 people (62.5%), whereas 12 respondents (37.5%) were skilled at performing endorphin massage techniques. Conclusion: Most respondents were able to carry out the endorphin massage technique to reduce menstrual pain. In adolescent girls include menstrual conditions, unbalanced nutritional intake, eating and drinking patterns, non-compliance with Fe tablet consumption and lack of knowledge.